Tax Procedure Code in the Czech Republic - Karfíková, Marie; Boháč, Radim (Public Governance, Administration and Finances Law Review, 2017)
The paper deals with Tax Procedure Code in the Czech Republic. The aim of this paper is to describe the Czech Tax Procedure Code and to present and evaluate its significant possible change. The basic principles of the Czech Tax Procedure Code are set out and the basic structure of the Tax Procedure Code is introduced. The study concludes that the tax procedure has been successfully codified in the Czech Republic. The adoption of Tax Procedure Code is a great achievement and the result of many years of work undertaken to preserve the autonomy of the tax procedure. Then the article is focused on the considered change of Tax Procedure Code related to the principle of tax self-assessment and tax additional self-assessment. It is further concluded that every tax in the broad sense should have a clearly stated model which is applicable for its assessment. Establishing the tax self-assessment and tax additional tax-assessment regime could make the examination stage of tax administration much clearer.